Seasonal and intradaily variations of Parietaria pollen in the atmosphere of Málaga. - Ruiz-Mata, Rocío; Trigo-Pérez, María del Mar; De-Gálvez-Montáñez, Enrique; Recio-Criado, María Marta; Muñoz-García, M.; Borgognone, Costanza; Picornell Rodríguez, Antonio (My University, 2023)
Parietaria pollen is one of the main causes of hay fever and asthma in the population, presenting a high allergenicity. That is why, in order to inform the population, it is important to determine whether its behaviour pattern is different in different parts of the city. The objective of this study was to analyze and compare the behaviour pattern of the Parietaria pollen type in two different points within the city of Malaga and to analyze the existing correlation between pollen concentrations and the main meteorological parameters. We used two Hirst-type volumetric pollen traps, one of them installed in the periphery and the other in the city center, between 2017 and 2019. The samples were mounted and counted following the recommendations of the Spanish Aerobiology Network. To calculate the annual pollen integral, the sum of the mean daily concentrations throughout the year was used. To calculate the intradaily variations, the values were accumulated every two hours, expressed as percentages of the daily total. In order to study the relationships between meteorological parameters and pollen concentrations, Spearman correlation tests have been carried out. The values of the annual pollen integral were always much higher in the centre. Daily mean concentrations showed the presence of this pollen type in the atmosphere throughout the year. Regarding the intraday pattern, a more pronounced peak was observed in the city centre, while in the periphery, the distribution is more homogeneous throughout the day. The meteorological parameters play an important role in determining the daily concentrations in the atmosphere. In the light of these results, we can conclude that it is necessary to install several sampling points within the same city, due to its heterogeneity and different land uses, in order to inform the population with a greater precision and, in this way, prevent respiratory allergies.
Keywords: Polen; Aparato respiratorio - Enfermedades inmunológicas; Alergia; Aerobiología; Alergias respiratorias